The role of spreading depolarization in subarachnoid hemorrhage - Sánchez-Porras, Renán; Zheng, Zelong; Santos, Edgar; Schöll, Michael; Unterberg, Andreas; Sakowitz, Oliver (European journal of neurology, 2013)
Subarachnoid hemorrhage (SAH) is a devastating disease associated with death and poor functional outcome. Despite decades of intense research and improvements in clinical management, delayed cerebral ischaemia (DCI) remains the most important cause of morbidity and mortality after SAH. The key role of angiographic cerebral vasospasm, thought to be the main cause of DCI, has been questioned. Emerging evidence suggests that DCI is likely to have a multifactorial etiology. Over the last few years, spreading depolarization (SD) has been identified as a potential pathophysiological mechanism contributing to DCI. The presence of cortical spreading ischaemia, due to an inverse hemodynamic response to SD, offers a possible explanation for DCI and requires more intensive research. Understanding the role of SD as another mechanism inducing DCI and its relationship with other pathological factors could instigate the development of new approaches to the diagnosis and treatment of DCI in order to improve the clinical outcome.